FORMULATION AND EVALUATION OF MECLIZINE HYDROCHLORIDE FAST DISSOLVING TABLETS USING SOLID DISPERSION METHOD - DARAVATH, BHASKAR; TADIKONDA, RAMA RAO (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The present research is aimed to investigate the effect of polyethylene glycol 4000 and 6000 as solid dispersions carriers on the solubility and dissolution rate of Meclizine hydrochloride. In this, meclizine hydrochloride solid dispersions were prepared using solvent evaporation method and evaluated for solubility studies, drug-carrier compatibility studies and in vitro dissolution studies. Formulations F4 and F8 were selected to prepare the tablets and compared with control tablets (conventional tablets using pure drug). From the in vitro dissolution studies, tablets containing polyethylene glycol 6000 showed almost complete drug release within the 20 min. The percent drug release in 20 min (Q20) and initial dissolution rate for formulation F8 was 99.26Â±1.62%, 4.96%/min. These were very much higher compared to control tablets (44.67Â±1.48 %, 2.23%/min). The relative dissolution rate was found to be 2.22 and dissolution efficiency was found to be 57.94 and it is increased by 3.0 fold with F8 formulation when compared to control tablets (22.05). In conclusion, formulation of the meclizine hydrochloride-polyethylene glycol solid dispersions is a suitable approach to improve the solubility and dissolution rate. Â Â Â Key Words: Dissolution efficiency, Initial dissolution rate, Polyethylene glycol, Relative dissolution rate, Solubility.